« Mais », entre figure de langue et figure de pensée dans le discours d’Emmanuel Macron - Kheira Djeradi (Multilinguales, 2023)
This article focuses on the language figures and thought figures punctuated by the use of the opposition connector « mais » in the interventions of Emmanuel Macron during the inter-round debate of the 2022 presidential elections against Marine Le Pen. Indeed, by the recurrent deployment of this connector, the candidate tried to ensure the effect of persuasion, clarity, nuance and above all, concessions in the process of argumentation. However, the perception and interpretation of recursion by voters can vary and may lead to other impacts, such as manipulation or bias. To limit this state of affairs, we propose to adopt the pragmatic conative approach. It will highlight the effectiveness of language figures in communication and their role in persuasion and meaning creation. It offers a deeper understanding of rhetoric by placing it at the centre of interactions.